2007
DOI: 10.1002/hep.21456
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic HNF4α deficiency induces periportal expression of glutamine synthetase and other pericentral enzymes

Abstract: In liver, most genes are expressed with a porto-central gradient. The transcription factor hepatic nuclear-factor4␣ (HNF4␣) is associated with 12% of the genes in adult liver, but its involvement in zonation of gene expression has not been investigated. A putative HNF4␣-response element in the upstream enhancer of glutamine synthetase (GS), an exclusively pericentral enzyme, was protected against DNase-I and interacted with a protein that is recognized by HNF4␣-specific antiserum. Chromatin-immunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 55 publications
10
76
1
Order By: Relevance
“…This response is transitory in nature because microarray analysis indicated that changes in cell cycle control and other genes involved in hepatocyte proliferation were associated with the Hnf4a F/F;AlbERT2cre knock-out and not with the Alb-Hnf4a Ϫ/Ϫ mice in which only small regenerating foci of hepatic periportal oval cells were observed previously (42). This latter finding was confirmed in the present study using BrdU incorporation.…”
Section: Discussionsupporting
confidence: 88%
“…This response is transitory in nature because microarray analysis indicated that changes in cell cycle control and other genes involved in hepatocyte proliferation were associated with the Hnf4a F/F;AlbERT2cre knock-out and not with the Alb-Hnf4a Ϫ/Ϫ mice in which only small regenerating foci of hepatic periportal oval cells were observed previously (42). This latter finding was confirmed in the present study using BrdU incorporation.…”
Section: Discussionsupporting
confidence: 88%
“…As both of these receptors have a positive effect on the Acot1 promoter, one would expect that the addition of activated PPARa and HNF4a may result in a synergistic increase in promoter activity. However, transcriptional regulation by HNF4a is accomplished by interactions with various coactivators or corepressors, such as histone deacetylase 1 (a corepressor), and a very recent study by Stanulovic et al (29) showed that both HNF4a and histone deacetylase 1 are present on an upstream enhancer element of the glutamine synthetase promoter, which results in the suppression of glutamine synthetase expression in liver periportal areas. Therefore, the competition between HNF4a and PPARa for binding to the Acot1 DR1 is likely a complicated interplay between coactivators, corepressors, and ligand availability.…”
Section: Discussionmentioning
confidence: 99%
“…6A), although some weak signal was detected in the knockout liver extracts. This may be attributable to the fact that HNF4a is a conditional liver-specific knockout and there is some very low amount of HNF4a protein present in the nucleus (29). EMSA was also performed using in vitrotranslated HNF4a, and binding to the DR1 was competed out using a 50-fold molar excess of cold probe and supershifted using an HNF4a antibody (Fig.…”
Section: The Acot1 Promoter Binds To Hnf4a In Vivo and In Vitromentioning
confidence: 99%
“…Clonal proliferation of positive nuclei can occasionally be observed at e18.5 in null livers (Fig. 6A and see also [19]). …”
Section: 6the Hnf4α-null Allele Presents the Same Characteristics mentioning
confidence: 74%